2000
DOI: 10.1128/jcm.38.7.2628-2632.2000
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Approach for the Serodiagnosis of Canine Lyme Disease by the Immunoblot Procedure

Abstract: Serum samples obtained from healthy, asymptomatic dogs in areas of Wisconsin and northern Illinois where Lyme disease is endemic or nonendemic were assayed for antibodies to Borrelia burgdorferi by enzyme-linked immunosorbent assay (ELISA), and positive results were confirmed by immunoblot assay. We found that 56.9% (562 of 1,077) of the samples were positive by ELISA and 82.0% (461 of 562) were positive by immunoblotting. A logistic regression model was developed to distinguish between nonvaccinated dogs natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
1
5
3
Order By: Relevance
“…OspA band was found in a relatively high proportion of our Western blot positive dogs (73%). This is in contrast with results obtained by Greene and Straubinber (2006), who mentioned it should not be normally detected in naturally infected dogs, and Guerra et al (2000) or Leschnik et al (2010), who detected it at low levels in dogs with natural infection (17 and 2% early infection (EI) -28% late infection (LI) in USA and Austria, respectively). BmpA (39 kDa) was found in our study in 55% of positive dogs, while other authors reported an occurrence of 88% (Guerra et al, 2000) and 26% (EI) -33% (LI) (Leschnik et al, 2010).…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…OspA band was found in a relatively high proportion of our Western blot positive dogs (73%). This is in contrast with results obtained by Greene and Straubinber (2006), who mentioned it should not be normally detected in naturally infected dogs, and Guerra et al (2000) or Leschnik et al (2010), who detected it at low levels in dogs with natural infection (17 and 2% early infection (EI) -28% late infection (LI) in USA and Austria, respectively). BmpA (39 kDa) was found in our study in 55% of positive dogs, while other authors reported an occurrence of 88% (Guerra et al, 2000) and 26% (EI) -33% (LI) (Leschnik et al, 2010).…”
Section: Discussioncontrasting
confidence: 89%
“…This is in contrast with results obtained by Greene and Straubinber (2006), who mentioned it should not be normally detected in naturally infected dogs, and Guerra et al (2000) or Leschnik et al (2010), who detected it at low levels in dogs with natural infection (17 and 2% early infection (EI) -28% late infection (LI) in USA and Austria, respectively). BmpA (39 kDa) was found in our study in 55% of positive dogs, while other authors reported an occurrence of 88% (Guerra et al, 2000) and 26% (EI) -33% (LI) (Leschnik et al, 2010). p58 and p18 bands, which were found in 50 and 9% of our positive cases, respectively, while being detected in 84 and 64% of cases, respectively, by Guerra et al (2000), have not been detected at all by Leschnik et al (2010).…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…The OspA antibodies usually are a marker for vaccination, but they may develop transiently in early infection, 83,85 or possibly later during chronic infections, as seen in infected humans, because Bb displays antigenic variation, and expresses its antigenic repertoire over time to avoid host immunity. [88][89][90][91] The C 6 result has been shown to wane after treatment; [92][93][94] OspF antibodies also may wane. 95 Determination of quantitative titers to C 6 (or potentially OspF), pre-and 3 94 to 6 months post-treatment, were recommended by 4/6 panelists to check for a decrease after treatment as an indicator of decreased antigenic load, and to establish a new baseline for future comparison, because qualitative tests may stay positive a long time after treatment.…”
Section: Topic 3amentioning
confidence: 99%